Pengaruh Penghargaan Finansial, Pertimbangan Pasar Kerja, Dan Nilai-Nilai Sosial Terhadap Minat Berkarir Menjadi Akuntan Publik - Suci, Denty Putri Wulan; Nugroho, Paskah Ika (Universitas Pendidikan Ganesha, 2024)
Public accounting is a profession that helps the public in providing information for decision-making, especially related to finance. The purpose of this research is to determine the factors that influence accounting students' interest in choosing the public accounting profession. The factors used in this research are financial rewards, job market considerations, and social values. The approach used is a quantitative approach with survey methods. The sample was taken using a sampling technique with as many as 85 accounting students from Satya Wacana Christian University, Salatiga, to fill out the questionnaire. Data processing in this study used SPSS 26 by testing multiple linear regression. Hypothesis testing uses the R square test and t test. The research results obtained by the R square test showed that the independent variable explained 18.5% of the dependent variable, while 81.5% was explained by other variables outside this research model. The results of the t-test concluded that H3 was accepted, while H1 and H2 were rejected.